Acute beetroot juice supplementation augments early neuromuscular performance after blood flow restriction: a crossover study in elite basketball players - Nie, Runsheng; Zhang, Gengyini; Kong, Junhao; Wang, Xi; Xie, Zhiyu; Lin, Lehai; Li, Tianhe; Liang, Yapu (Frontiers in Nutrition, 2026)
IntroductionBeetroot juice (BJ), rich in nitrate, has been shown to enhance exercise performance via nitric oxide-mediated pathways. While its effects on endurance and strength have been studied, its influence on blood flow restriction (BFR)-induced post-activation potentiation (PAP) remains unclear.MethodsTwenty elite male basketball players (aged 21.25 ± 1.77 years) completed a randomized, double-blind, placebo-controlled crossover trial. Participants ingested BJ (8.4 mmol nitrate) or placebo before performing a standardized warm-up and BFR-assisted plyometric protocol. Counter-movement jump (CMJ) variables were recorded at baseline and at 0, 4-, 8-, 12-, and 16-min post-intervention. A two-way repeated-measures ANOVA was used to assess condition, time, and interaction effects, supplemented by Bonferroni-corrected paired t-tests and effect size analysis, with significance set at p ≤ 0.05.ResultsBJ significantly increased jump height calculated from take-off velocity [H(v)], peak power (PP), and peak rate of force development (PRFD) during the first 8 min post-intervention compared to placebo. Placebo showed higher H(v) at 12 min. Some variables showed moderate effect sizes without statistical significance, likely due to limited power. No performance benefits were observed in either condition at 16 min.ConclusionAcute BJ intake synergizes with BFR-induced PAP to transiently enhance neuromuscular performance, particularly within an early 8-min window. However, the effects are time-sensitive and may not extend or outperform placebo at later stages. These findings support a targeted, time-optimized use of BJ in warm-up strategies for explosive performance.